Targetable Brg1‐CXCL14 axis contributes to alcoholic liver injury by driving neutrophil trafficking - Nan Li; Hong Liu; Yujia Xue; Zheng Xu; Xiulian Miao; Yan Guo; Zilong Li; Zhiwen Fan; Yong Xu (EMBO Molecular Medicine)
Abstract Alcoholic liver disease (ALD) accounts for a large fraction of patients with cirrhosis and hepatocellular carcinoma. In the present study we investigated the involvement of Brahma‐related gene 1 (Brg1) in ALD pathogenesis and implication in ALD intervention. We report that Brg1 expression was elevated in mouse models of ALD, in hepatocyte exposed to alcohol, and in human ALD specimens. Manipulation of Brg1 expression in hepatocytes influenced the development of ALD in mice. Flow cytometry showed that Brg1 deficiency specifically attenuated hepatic infiltration of Ly6G+ neutrophils in the ALD mice. RNA‐seq identified C‐X‐C motif chemokine ligand 14 (CXCL14) as a potential target for Brg1. CXCL14 knockdown alleviated whereas CXCL14 over‐expression enhanced ALD pathogenesis in mice. Importantly, pharmaceutical inhibition of Brg1 with a small‐molecule compound PFI‐3 or administration of an antagonist to the CXCL14 receptor ameliorated ALD pathogenesis in mice. Finally, a positive correlation between Brg1 expression, CXCL14 expression, and neutrophil infiltration was detected in ALD patients. In conclusion, our data provide proof‐of‐concept for targeting the Brg1‐CXCL14 axis in ALD intervention.